Acute blood glucose fluctuation enhances rat aorta endothelial cell apoptosis, oxidative stress and pro-inflammatory cytokine expression in vivo. Issue 1 (December 2016) - Wu, Na; Shen, Haitao; Liu, Henan; Wang, Yanjun; Bai, Yu; Han, Ping
Abstract Background Complications of diabetes mellitus (DM) are related not only to elevated plasma glucose, but also plasma glucose fluctuations. However, the specific mechanism underlying the role of plasma glucose fluctuation in the pathogenesis of DM complications remains poorly understood. In the present study, the influence of acute fluctuant hyperglycemia and persistent hyperglycemia on vascular endothelial cell apoptosis, function, oxidative stress and inflammation was examined in vivo. Methods Rats were assigned to three different groups (n = 10/group) that received 48-h infusions of saline (SAL group), continuous 50 % glucose (constant high glucose group [CHG]), or intermittent 50 % glucose (acute blood glucose fluctuation group [AFG]). Plasma 8-isoprostaglandin, interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α) and intercellular adhesion molecule-1 (ICAM-1) levels were quantified by using enzyme-linked immunosorbent assay (ELISA) commercial kits. Plasma insulin levels were measured by radioimmunoassays (RIAs) using kits. The aortic segment was collected. The levels of malondialdehyde (MDA) and activity of glutathione peroxidase (GSH-PX) were measured in endothelial homogenates prepared from endothelial cells harvested from the aorta using colorimetric kits. Apoptosis of vascular endothelial cells was determined with terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL). Endothelial dysfunction was assessed by isometric tension recording to evaluate the endothelial function. The expression of B cell lymphoma-2 (Bcl-2), Bcl-2 Associated X protein (Bax), pro caspase-3, caspase-3 p17, 3-nitrotyrosine (3-NT) and p47phox protein in rat aortic endothelial cells were tested with Western blot analysis. Endothelial cells reactive oxygen species (ROS) formation was determined using dihydroethidium-dependent fluorescence microtopography in aortic cryo-sections. Expression of IL-6, TNF-α and ICAM-1 mRNAs in vascular endothelial cells were determined by real-time quantitative PCR. Results Endothelial cells apoptosis and dysfunction were observed significantly in the aortas of the AFG group (P < 0.05). The AFG had reduced Bcl-2 and pro caspase-3 levels and enhanced Bax mitochondrial translocation and caspase-3 p17 protein levels in comparison with the CHG group (P < 0.05). Both AFG and CHG induced β-cell dysfunction and insulin resistance (P < 0.05). AFG increased MDA and 8-isoprostaglandin levels in plasma, oxidative stress in vascular endothelial cells, and inflammatory cytokines in plasma and vascular endothelial cells (P < 0.05). Conclusion Acute glucose fluctuation may cause significant oxidative stress and inflammation in endothelial cells, increase the adhesion of monocytes to endothelial cells, and elevate endothelial cell apoptosis, resulting in severe cardiovascular injury.